Hormone beefs, chloridric chicken and international trade: Can scientific uncertainty be an informational barrier to trade? - Giacomo Calzolari; Giovanni Immordino (Fondazione Eni Enrico Mattei (FEEM), 2000)
We study international trade of innovative goods subject to scientific uncertainty on consumers' health effects. Trade of these goods is often at the centre of international disputes. We show that a new trade protectionism may arise because of the scientific uncertainty. A free riding effect is individuated implying a more conservative behaviour by countries. We also study the informative role played by producers (lobbies) in revealing valuable information. We find that producers reveal more information when the effects of harmful consumption on health are long lasting. Our results are robust to several extensions (e.g. product labelling, firm liability).
Keywords: D8; F1; L1; 330; International trade; lobbies; information; scientific uncertainty; Lebensmittelsicherheit; Gesundheitsrisiko; Handelshemmnisse; Außenhandelspolitik; Protektionismus; Interessenpolitik; Spieltheorie; Signalling; Theorie